A Review on Polymer and Lipid-Based Nanocarriers and Its Application to Nano-Pharmaceutical and Food-Based Systems - Lu, Hongyun; Zhang, Shengliang; Wang, Jinling; Chen, Qihe (Frontiers in Nutrition, 2021)
Recently, owing to well-controlled release, enhanced distribution and increased permeability, nanocarriers used for alternative drug and food-delivery strategies have received increasingly attentions. Nanocarriers have attracted a large amount of interest as potential carriers of various bioactive molecules for multiple applications. Drug and food-based delivery via polymeric-based nanocarriers and lipid-based nanocarriers has been widely investigated. Nanocarriers, especially liposomes, are more and more widely used in the area of novel nano-pharmaceutical or food-based design. Herein, we aimed to discuss the recent advancement of different surface-engineered nanocarriers type, along with cutting-edge applications for food and nanomedicine and highlight the alternative of phytochemical as nanocarrier. Additionally, safety concern of nanocarriers was also highlighted.